Perancangan Bisnis Token Untuk Trading Card Game - Kimberly Noviana; Hutomo Setia Budi (Universitas Ciputra Surabaya, 2018)
Trading Card Game is a card game used for collection and play. In the game Card Trading Game has many types of cards in the game, one of which is Token. A token is a secondary card to represent something while the game is in progress. However, not all Trading Card Game players need to use this card. The purpose of this research is to know the opinion of Trading Card Game players regarding the use of Token card, and the business opportunity that can be achieved as Token card manufacturer. The population of this research is Trading Card Game Players across Indonesia, which are separated into 2 groups. The specified subject is specified only for members of the Trading Card Game community, which consists of 100 players of Trading Card Game and 5 experts in Trading Card Game. This research is done by qualitative and quantitative method toward the research object.Direct observation data collection tools as well as distributing questionnaires conducted using online media assistance. The results of this study concluded the importance of having a Token in Trading Card Game, and there is a good opportunity to market Trading Card Game Token type card.